A case report of granulomatous amoebic encephalitis by Group 1 Acanthamoeba genotype T18 diagnosed by the combination of morphological examination and genetic analysis - Takahiro Matsui; Tetsuo Maeda; Shinsuke Kusakabe; Hideyuki Arita; Kenji Yagita; Eiichi Morii; Yuzuru Kanakura (Diagnostic Pathology, 2018)
Abstract Background The diagnosis of granulomatous amoebic encephalitis is challenging for clinicians because it is a rare and lethal disease. Previous reports have indicated that Acanthamoeba with some specific genotypes tend to cause the majority of human infections. We report a case of granulomatous amoebic encephalitis caused by Acanthamoeba spp. with genotype T18 in an immunodeficient patient in Japan after allogenic bone marrow transplantation, along with the morphological characteristics and genetic analysis. Case presentation A 52-year old man, who had undergone allogenic bone marrow transplantation, suffered from rapid-growing brain masses in addition to pneumonia and died within 1 month from the onset of the symptoms including fever, headache and disorientation. Infection with Acanthamoeba in the brain and lung was confirmed by histological evaluation; immunohistochemical staining and polymerase chain reaction analysis using autopsy samples also indicated the growth of Acanthamoeba in the brain. Gene sequence analysis indicated that this is the second documented case of infection with Acanthamoeba spp. with genotype T18 in a human host. Postmortem retrospective evaluation of cerebrospinal fluid sample in our case, as well as literature review, indicated that some cases of granulomatous amoebic encephalitis caused by Acanthamoeba may be diagnosable by cerebrospinal fluid examination. Conclusion This case indicates that Acanthamoeba spp. with genotype T18 can also be an important opportunistic pathogen. For pathologists as well as physicians, increased awareness of granulomatous amoebic encephalitis is important for improving the poor prognosis along with the attempt to early diagnosis with cerebrospinal fluid.